Aggregation of luteinizing hormone receptors in granulosa cells: a possible mechanism of desensitization to the hormone. - Amsterdam, A (1980)
The temporal relationship between redistribution of receptors to lutropin (luteinizing hormone)/human chorionic gonadotropin in cultured rat ovarian granulosa cells and the cellular response to hormonal challenge were studied. Visualization of receptor-bound human chorionic gonadotropin by indirect immunofluorescence, with hormone-specific antibodies after fixation with 2% formaldehyde, revealed the existence of small clusters around the entire cell circumference 5--20 min after exposure to the hormone at 37 degrees C. Such small receptor aggregates were also evident if hormone incubation was at 4 degrees C or if cells were fixed with 2% formaldehyde before incubation. Larger clusters were evident after prolonged incubation with the hormone (2--4 hr) at 37 degrees C. The later change coincided with diminished cyclic AMP accumulation in respose to challenge with fresh hormone. When the fixation step was omitted and antibodies to human chorionic gonadotropin were applied after hormonal binding, acceleration of both receptor clustering and the desensitization process was observed. This maneuver also induced capping of the hormone receptors. In contrast, monovalent Fab' fragments of the antibodies were without effect. Internalization of the bound hormone in lysosomes, and subsequent degradation, was evident 8 hr after hormonal application and was not accelerated by the antibodies. It is suggested that clustering of the luteinizing hormone receptors may play a role in cellular responsiveness to the hormone. Massive aggregation of the receptors may desensitize the cell by interferring with coupling to adenylate cyclase.